2011
DOI: 10.1016/j.tox.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil hydroxytyrosol reduces toxicity evoked by acrylamide in human Caco-2 cells by preventing oxidative stress

Abstract: Humans are exposed to dietary acrylamide (AA) during their lifetime, it is therefore necessary to investigate the mechanisms associated with AA-induced toxic effects. Accumulating evidence indicates that oxidative stress contributes to AA cytotoxicity, thus, dietary antioxidants might have a protective role in colonic cells against AA toxicity. We have recently reported that hydroxytyrosol (HTy), a natural antioxidant abundant in olive oil, is able to enhance the cellular antioxidant defence capacity, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
5
37
0
1
Order By: Relevance
“…Furthermore, a significant increase in the MPO which removes H 2 O 2 and catalyzes the formation of toxic hypochlorous acid that leads to neutrophil infiltration and oxidative damage has been reported by Mustafa et al [13]. The present data is consistent with the previous study reporting that in the hepatic Caco-2 intestinal cells, AA induced oxidative stress through depletion of GSH, overproduction of ROS, and induction of apoptosis biomarkers that resulted in cell death [14].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a significant increase in the MPO which removes H 2 O 2 and catalyzes the formation of toxic hypochlorous acid that leads to neutrophil infiltration and oxidative damage has been reported by Mustafa et al [13]. The present data is consistent with the previous study reporting that in the hepatic Caco-2 intestinal cells, AA induced oxidative stress through depletion of GSH, overproduction of ROS, and induction of apoptosis biomarkers that resulted in cell death [14].…”
Section: Discussionsupporting
confidence: 93%
“…A few resorption lacunae were identified in these mice in pars anterior of the periosteal border. According to several authors [8][9]15] AA increases the oxidative stress and peroxidation of the lipids. The oxidative stress causes an increased production of reactive oxygen species (ROS) [16], which enhance osteoclastic activity [17] and bone resorption [18].…”
Section: Resultsmentioning
confidence: 99%
“…In human erythrocytes (in vitro), AA increases hemolysis and lipid peroxidation [8], suggesting that this neurotoxin affects redox status in cells [9]. The reported oral LD50 value is 107 mg/kg body weight (b.w.)…”
Section: Introductionmentioning
confidence: 99%
“…The average daily intake of acrylamide for adults is approximately 0.5 mg/kg body weight; children may have two to three times more intake than adults (18,38,55 exposed people at a lifelong intake of 0.08 mg/kg body weight/day (47). Rodriguez-Ramiro et al have shown that smaller doses of acrylamide can act as toxicant when administered in long-term exposure (48). Therefore, it cannot be ruled out that daily exposure to a lower dose of acrylamide may bring forth a risk factor of toxicity in humans.…”
Section: Discussionmentioning
confidence: 99%